Breast cancer and physical activity: A bibliometric analysis - Fresno-Alba, S.; Denche-Zamorano, Á.; Pastor-Cisneros, R.; Pereira-Payo, D.; Franco-García, J. M.; Jiménez-Castuera, R. (Frontiers in Oncology, 2023)
Breast cancer is a pathology suffered by millions of women worldwide, affecting mental health, quality of life (QoL), physical functioning, cognitive functioning, social and work life of surviving patients. Moreover, breast cancer is associated with weigh gain, muscle atrophy, and weakness. quality appears to be an effective non-pharmacological treatment to improve short-term self-esteem QoL, fatigue, and psychological factors such as depression, anxiety, happiness, and body image. The practice of physical activity is associated with a reduction in side effects of treatment also. This bibliometric analysis analysed the trend followed by publications on breast cancer and physical activity. The Web of Science database was used, and bibliometric laws were applied to identify the most prolific authors, the journals most involved in the field, as well as the countries, institutions, and keywords most used by the authors. Breast cancer and physical activity have an exponential trend in the number of publications, with Psycho-Oncology being the journal with the highest number of publications.